Analisis Maqashid Syariah terhadap Pasal 8 PP No 10 Tahun 1983 Jo PP 45 Tahun 1990 tentang Nafkah ‘Iddah Isteri setelah Ditalak Suami - Mukhlis Bakri (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2023)
This study examines the Maqashid Sharia Analysis of the Wife's Iddah Income After Her Husband Divorced Based on Article 8 PP No. 10 of 1983 Jo PP 45 of 1990. The formulation of the problem from this research is how is the concept of Iddah's livelihood in article 8 of PP No. 10 of 1983 Jo PP 45 of 1990 and how to analyze the concept of Maqashid Syariah against article 8 PP No.10 of 1983 Jo PP 45 of 1990. The method used in this research is a type of qualitative research, with the type of research used is library research (Library Research) or indirect observation. This research has the following results: Whereas in the PP it is stated that civil servant husbands must provide maintenance to their divorced wives, in which this income is provided according to established regulations. Meanwhile, in Maqashid Syariah, the maintenance given by the ex-husband to the ex-wife is as long as the ex-wife is carrying out the iddah period in talak raj'i.